Penguatan Profesionalisme Guru Matematika SMP melalui Pelatihan Pengembangan Video Pembelajaran Interaktif Berbasis Canva Berorientasi Deep Learning di MGMP Matematika Lombok Barat - Tabita Wahyu Triutami; Arjudin Arjudin; Sri Subarinah; Syahrul Azmi; Muhammad Turmuzi; Laylatul Hisda (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service program aimed to improve the professionalism of junior high school mathematics teachers through training on developing interactive learning videos using Canva oriented toward deep learning. The program was conducted in the Mathematics Teachers’ Working Group (MGMP) of West Lombok through several stages, including preparation of training materials, program socialization, training implementation, classroom application, mentoring, and evaluation. The training materials covered the concept of deep learning, the use of Canva as an IT-based learning medium, and practical activities in creating interactive mathematics learning videos. Evaluation was carried out using questionnaires to determine participants’ responses and understanding of the training activities. The results showed that participants gave positive responses to all aspects of the training. Teachers experienced improvements in understanding, creativity, and skills in developing interactive learning media using Canva. Furthermore, the training supported the implementation of more engaging, innovative, and student-centered mathematics learning.